Interactive Multimedia Assisted Direct Learning to Improve Student's Understanding of Fluid Concepts - Hermansyah Hermansyah; Fahmi Yahya; Syarif Fitriyanto; Wahyu Indah Widya Astuti; Ory Auliah (Physics Education Research Journal, 2022)
The use of appropriate media is minimal in physics learning today, which impacts students' lack of motivation and indirectly affects their learning outcomes. A direct learning model with interactive multimedia is an alternative solution during the current pandemic. This study aims to improve students' understanding of physics concepts by applying a direct learning model with interactive multimedia. This is a quasi-experimental research with a pretest-posttest control group design using a purposive sampling technique. Forty-five respondents were divided into two groups, experimental and control. N-Gain was used to determine the high increase in both groups. The test was used to collect data on students' conceptual understanding in the form of a description with a total of 5 questions. In addition to the N-Gain, a t-test was also conducted to test the mean difference of the data. The findings revealed that the understanding of the concepts of the two groups had increased, where the experimental group was 40.3, and the control group was 35.8 but did not differ significantly. It can be concluded that the understanding of the fluid concept of the experimental class students is not better than the control class students.